Dampak Kepemilikan Pesisir Laut yang dijadikan Objek Wisata (International Forum of Researchers and Lecturers, 2024)
This research aims to find out the impact of owning coastal areas which are used as tourist attractions. This research is empirical research because it places primary data in the community as the main data which is analyzed descriptively qualitatively. The results of the research show that the impact of ownership of coastal areas that are used as tourist attractions triggers violations because this control is linked to the control of coastal areas of indigenous communities, and is then recognized by law. This then results in a conflict of interest because coastal people tend to carry out activities and work at sea, and utilize these aquatic resources as a target to fulfill their daily needs. The economic activities of residents on the coast who tend to work as fishermen and farmers are certainly not used to other activities. Meanwhile, tourism development in villages that have the potential for beautiful marine and coastal resources generally aims to introduce and utilize, even improve the quality of natural objects and attractions. This then also causes losses to the government and local communities because apart from having an impact on the physical environment which experiences a decline due to human activity at the tourist location itself, all income and benefits are also received in full by the business owner. In this condition, the village government does not get any share, because tourist attractions are recognized as private property.